Process and benefits of community-led multiple use water services: comparing two communities in South Africa - van Koppen, Barbara; Magombeyi, Manuel Simba; Jacobs-Mata, Inga; Molose, V.; Phasha, K.; Bophela, T.; Modiba, I.; White, M. (International Water Management Institute, 2020)
The African Water Facility, together with the Water Research Commission, South Africa, as its implementing agent, supported the demonstration project Operationalizing community-led Multiple Use water Services (MUS) in South Africa. As knowledge broker and research partner in this project, the International Water Management Institute (IWMI) analyzed processes and impacts at the local level, where the nongovernmental organization Tsogang Water and Sanitation demonstrated community-led MUS in six diverse rural communities in two of the poorest districts of South Africa, Sekhukhune and Vhembe districts - Ga Mokgotho, Ga Moela and Phiring in the Sekhukhune District Municipality, and Tshakhuma, Khalavha and Ha Gumbu in Vhembe District Municipality. In conventional water infrastructure projects, external state and non-state agencies plan, diagnose, design and prioritize solutions, mobilize funding, and implement the procurement of materials, recruitment of workers and construction. However, this MUS project facilitated decision-making by communities, and provided technical and institutional advice and capacity development. Based on IWMI’s evidence, tools and manuals, the project team organized learning alliances and policy dialogues from municipal to national level on the replication of community-led MUS by water services authorities; government departments of water, agriculture, and others; employment generation programs; climate and disaster management; and corporate social responsibility initiatives.